POPULASI DAN KARAKTERISTIK HABITAT KATAK KONGKANG JERAM (Huia masonii) DI KALI KUNING TAMAN NASIONAL GUNUNG MERAPI - , CAHYANDRA TRESNO A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Herpetofauna research especially amphibian in Gunung Merapi National Park was lead to diversity index. It has not specified in a certain species population. Javan Torrent Frogs (Huia masonii) are one of the endemic frogs in Java, with vulnerable status in IUCN classification. One of its distributions is in Kali Kuning (Kuning river), Gunung Merapi National Park. This river is threatened by land changing because of mount Merapi explosion. This research was designed to investigate the population estimation and habitat characteristics of Javan Torrent Frogs (Huia masonii) in Kali Kuning, Gunung Merapi National Park. This research was carried out over a period of two months (October- November 2012). The method used to collect data was the mark-recapture method with a line transect of two kilometers along the river. Captured frogs were tagged using modified shoelaces. Habitat data was collected each 100 m along the river (two kilometers). The population estimation of Huia masonii was calculated with the Schnabel method, and habitat characteristics were analyzed descriptively and quantitatively. The results showed that the population estimate of Huia masonii was 82 individuals (ranging form 60 to 120 individuals) or 12 individuals/hectare (ranging form 9 form 17 individuals/hectare). Huia masonii habitat in Kuning River includes a torrenting river which flows all year round. The average water velocity was 0,62 m/s and average debit was 0,43 m3/s with a cover dominated by rocks at a height of 797 m asl to 907 m asl. Water was clear with neutral acidity. The average water temperature was 21.6 0C, average air temperature was 21,3 0C, and average air humidity was 78 %. The average of ground cover was 31.67% which was dominated by Sintrong (Crassocephalum crepidioides), Kolonjono (Pennisetum purpureum), Wedusan (Ageratum conyzoides), and Irengan (Conyza maxima). Ground cover have a positive impact on Huia masonii in Kuning River.